2012
DOI: 10.1038/aps.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin alleviates ER stress via activating AMPK

Abstract: Aim: To investigate the protective effects of arctigenin (ATG), a phenylpropanoid dibenzylbutyrolactone lignan from Arctium lappa L (Compositae), against ER stress in vitro and the underlying mechanisms. Methods: A cell-based screening assay for ER stress regulators was established. Cell viability was measured using MTT assay. PCR and Western blotting were used to analyze gene and protein expression. Silencing of the CaMKKβ, LKB1, and AMPKα1 genes was achieved by RNA interference (RNAi). An ATP bioluminescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…To investigate whether there was any connection between ER stress and ERRγ, AML12 (Mouse hepatoma cell line) cells were treated with known ER stress inducers, Tm, Thapsigargin (45) and Brefeldin A (52). A significant increase in the ERRγ mRNA level was observed by qRT-PCR, though there was no significant increase in ERRα and ERRβ mRNA level (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether there was any connection between ER stress and ERRγ, AML12 (Mouse hepatoma cell line) cells were treated with known ER stress inducers, Tm, Thapsigargin (45) and Brefeldin A (52). A significant increase in the ERRγ mRNA level was observed by qRT-PCR, though there was no significant increase in ERRα and ERRβ mRNA level (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…AMPK activation has been reported to attenuate ER stress in various cell types (Gu et al, 2012, Salvado et al, 2013, Wang et al, 2011. Autophagy helps the cell to adapt to stress through clearance of misfolded proteins and damaged organelles (Ogata et al, 2006).…”
Section: Ctrp9 Induces Autophagy Through Ampk Activation In Hepg2 Celmentioning
confidence: 99%
“…However, it has also been reported that cells undergo autophagy-induced cell death, if the stress is beyond their comprehension. Previous studies have indicated that arctigenin induces autophagy, which can lead to the death of several cell lines (11,20,(29)(30)(31). Therefore, in this study, to examine the autophagic activity of MCF-7 cells in response to arctigenin treatment, we analyzed the conversion of LC3 (LC3-I) into LC3-II.…”
Section: Resultsmentioning
confidence: 99%